Implementation of the Triple Bottom Line Accounting Concept at Hotel X - Yudhistira, Bintang; Wiryanata, I Gusti Ngurah Agung; Rukmiyati, Ni Made Sri (Indonesian Journal of Banking and Financial Technology, 2024)
Environmental and social responsibility is a form of company commitment to the sustainability of tourism in the future. The company does not only focus on profit but also on people and planet, in accordance with the Triple Bottom Line concept. This study aims to determine the implementation of the Triple Bottom Line Accounting concept at Hotel X. This study uses qualitative descriptive analysis techniques and focuses on the scope of the implementation of the Triple Bottom Line Accounting concept in environmental, social and tourism responsibility activities. The data collection procedure is carried out through interviews, observations, and documentation studies. This study uses the Triple Bottom Line Accounting concept by Elkington. The results of this study indicate that Hotel X has implemented the Triple Bottom Line Accounting concept well. The concept of planet, people and profit is implemented through various sustainability programs. Hotel X charges costs for environmental and social activities as hotel cost burdens. Hotel X does not only focus on profit, but also on the natural and social environment of the community.